2007
DOI: 10.1242/dev.02653
|View full text |Cite
|
Sign up to set email alerts
|

β-Spectrin functions independently of Ankyrin to regulate the establishment and maintenance of axon connections in theDrosophilaembryonic CNS

Abstract: DEVELOPMENT 273 RESEARCH ARTICLE INTRODUCTIONDuring central nervous system (CNS) development, growth cones navigate a series of choice points to find their appropriate targets. These guidance decisions are shaped by a balance of attractive and repulsive cues found in the extracellular environment that can act locally or at a distance (Tessier-Lavigne and Goodman, 1996). Slit ligands and Robo receptors play conserved roles in regulating midline axon crossing in both invertebrate and vertebrate nervous systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Because wild-type Slit levels are required to position the longitudinal fascicles, a reduction of slit gene dosage results, as expected, in a further medial positioning of the longitudinal connectives, explaining the increase in the number of ectopic midline crosses in these animals. Similar phenotypes were also observed by Garbe et al (Garbe et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Because wild-type Slit levels are required to position the longitudinal fascicles, a reduction of slit gene dosage results, as expected, in a further medial positioning of the longitudinal connectives, explaining the increase in the number of ectopic midline crosses in these animals. Similar phenotypes were also observed by Garbe et al (Garbe et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…We also note that in Drosophila, the genetic loss of a-spectrin leads to a redistribution and mislocalization of b-spectrin (Garbe et al, 2007).…”
Section: Deletion Of Aii-spectrin 3959mentioning
confidence: 61%
“…4C). This defect can be rescued by providing robo function specifically in the ap neurons in an otherwise mutant background, indicating that Robo guides later projecting neurons independently of its earlier function in the longitudinal pioneers (Garbe et al, 2006). Interestingly, a time course analysis has shown that midline crossing defects in the ap neurons can arise at two different times.…”
Section: Robo Repels Specific Subsets Of Ipsilateral Axons Independenmentioning
confidence: 99%
“…Previous studies have established that the axon guidance phenotypes of both robo and fra can be significantly rescued by expressing these genes in postmitotic neurons using the Gal4-UAS system (Kolodziej et al, 1996;Kidd et al, 1998a;Garbe et al, 2006). Therefore, we tested whether transgenic expression of either Fra or Robo in the double mutants would "rescue" the phenotype and restore it to one that more closely resembled the single mutants (Fig.…”
Section: Neuronal Expression Of Either Robo or Fra In The Double-mutamentioning
confidence: 99%
See 1 more Smart Citation